Local forest specialists maintain traditional ecological knowledge in the face of environmental threats to Brazilian Amazonian protected areas - Alves, Rubana Palhares; Levis, Carolina; Bertin, Vinicius Mutti; Ferreira, Maria Julia; Cassino, Mariana Franco; Pequeno, Pedro Aurélio Costa Lima; Schietti, Juliana; Clement, Charles R. (Frontiers in Forests and Global Change, 2022)
There is a concern that environmental threats that result in local biodiversity loss compromise traditional peoples’ livelihoods and their traditional ecological knowledge (TEK). Nonetheless, studies usually only analyze how people's characteristics influence TEK. Here, we investigated both: how the personal characteristics of local specialists (forest experience, gender, origin) and environmental threats (deforestation, mining, fires) influence some components of TEK associated with forests. From 2015 to 2019, we conducted free-listing interviews with 208 specialists from 27 communities in and near ten protected areas in Brazilian Amazonia. We recorded forest trees and palms that the specialists mentioned as used, managed, and traded. Plant knowledge was variable, since 44 % of the 795 ethnospecies were mentioned only once. Using generalized linear mixed-effects models, we identified that people with longer forest experience and men tended to cite more used and traded ethnospecies. Women knew more about human food, while men knew more about construction and animal food. Specialists with greater forest experience knew more about protective management and planting. Specialists living in communities influenced by mining cited fewer used ethnospecies, and those in more deforested communities cited more planting. Environmental threats had smaller effects on TEK than personal characteristics. The components of TEK that we assessed highlight the forest's great utility and the importance of management of protected areas to maintain biodiversity and traditional people's livelihoods. The communities' stocks of TEK persisted in the face of environmental threats to protected areas, highlighting the resistance of traditional peoples in the face of adversities. This quantitative approach did not show the trends that are generally imagined, i.e., loss of forest TEK, but demonstrates that if we want to change the Amazonian development model to keep the forest standing, knowledge exists and resists.